Clastogenic effects on bone marrow erythrocytes of some medicinal plants - Lim-Sylianco, Cy; Panizares, I.; Jocano, A.P (1985)
Clastogenic effects of chromosome-breaking effects of some medicinal plants were investigated using the micronucleus test of the seventeen antiarthritics, "Malunggay" and " Siling labuyo" were shown to cause the formation of micronucleated polychromatic erythrocytes at a range which is twice that of the control level. None of the six antiasthmatics exhibited chromosome breaking effects. The same observation was madeon four antifungal, two antihemorrhoids, two antihypertensives, one antimalarial, three antipruritics, four antiseptics, five antringents, four plants for contusions, fourteen palnts for skin ulcers, five for nausea and vomiting, five diuretics, nine laxatives, seven plants for fainting an seven plants for headcahes. Of the antitusives and antipyretics, only "mamalis" was clastogenic to a small extent. Of the carminatives, "Ikmo" and "siling labuyo" caused an appreciable formation of micronucleated polychromatic erythrocytes. Of the skin counterirritants, only "ikmo" showed clastogenic effects.